PENGEMBANGAN MODEL SaV BERBASIS SIMBOLIK PENDEKATAN ADDIE UNTUK MENINGKATKAN PENGUASAAN MATERI KULIAH STRATEGI PEMBELAJARAN - Cahyo Apri Setiaji; Anita Rinawati (Universitas Muria Kudus, 2022)
The purpose of this development research is to create a new product in the form of a Symbol and Visits (SaV) learning model as well as to test the level of effectiveness in improving the mastery of teaching materials for the Learning Strategy course. The research method uses the ADDIE approach with the stages of analysis, design, development, implementation, and evaluation. Research data were collected using documentation and test methods. The data collected in this research uses documentation, observation, interview, and test techniques. The research sample was 14 students of the Economic Education Study Program for the limited trial, 28 for the broad trial, and 62 for the operational test. The results of the study in the form of data were analyzed using qualitative and quantitative descriptive. Qualitative descriptive was conducted by analyzing pre-survey data and internal design testing. The quantitative analysis consisted of a limited trial, a broad trial, and an operational trial. Student learning outcomes at the operational test stage obtained an average value of 83.61, an increase compared to the limited trial of 70.92, and the broad trial of 81.42. The results showed that the development of the SaV model was able to improve the mastery of teaching materials in the Learning Strategy course for students of the Economic Education Study Program, University of Muhammadiyah Purworejo.